REDESIGNING LITHIUM BATTERY PRODUCTS AND APPLYING THE BUSINESS MODEL CANVAS WITH A LEAN STARTUP APPROACH (CASE STUDY: PT. BATEX ENERGI MANDIRI) - Rahmatullah, Hasan Ravi; Sutopo, Wahyudi; Rochani, Renny (Jurnal Ilmiah Teknik Industri, 2024)
Indonesia is experiencing rapid growth in the number of motorized vehicles, which increases the need for lithium batteries as an efficient energy storage solution, where startups such as PT Batex need to face the challenges of innovation and market understanding through lean startup methods to improve their products and competitiveness in the industry. This research focuses on redesigning lithium battery batteries to create innovative products that are successful in the market by considering customer needs, business feasibility, and the application of lean startup methods while addressing the challenge of lack of product innovation. This research method uses a qualitative approach with stages including problem identification, data collection through observation, interviews, and prototype testing. Furthermore, analysis is carried out to evaluate product development results and integrate customer feedback into the final design. The redesign of lithium battery batteries by PT Batex shows success with a durability of up to 3,000 charging cycles, a customer satisfaction rate of 90%, and an increase in market share from 5% to 15% in one year. In the future, more in-depth market analysis and research on integrating lithium battery batteries with renewable energy systems will be needed to support sustainability and product development.